Copper-based monolithic catalyst with carbon layer protection and preparation method thereof

By using a copper-based monolithic catalyst with carbon layer protection, the problems of pulverization and complex processes of existing catalysts during on-board use are solved, and efficient and stable hydrogen production reaction of methanol water vapor reforming is achieved.

CN117299167BActive Publication Date: 2025-04-04ZHEJIANG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311223759.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-04
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

The existing methanol hydrogen production catalyst is prone to powder during on-board use, resulting in excessive pressure drop and limited mass transfer. At the same time, the loading process is complicated and the uneven heat transfer of the reactor affects production capacity.

Method used

A copper-based monolithic catalyst with carbon layer protection is used to chelate the copper salt and the support metal salt through an alcohol compound, and heat treatment is carried out under a non-oxidizing atmosphere to form a copper-based catalyst powder coated with a carbon layer, and is raw material with a binder, a pore-forming agent and silicon carbide. After ball milling, dry press molding and high-temperature sintering, a copper-based monolithic catalyst is prepared.

Benefits of technology

It improves the catalytic performance and stability of the catalyst, extends the service life, simplifies the preparation process, and significantly improves the methanol conversion rate and hydrogen selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117299167B_ABST
    Figure CN117299167B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a copper-based monolithic catalyst with carbon layer protection, comprising: using copper-based catalyst powder with carbon layer protection, a binder, a pore-forming agent and silicon carbide as raw materials, ball-milling and mixing the raw materials evenly, and then dry-pressing and high-temperature sintering to obtain a copper-based monolithic catalyst; the method for preparing copper-based catalyst powder with carbon layer protection comprises: mixing a copper salt solution and a precursor solution of a carrier metal salt, adding an alcohol compound, and drying to obtain a catalyst precursor; heat-treating the catalyst precursor in a non-oxidizing atmosphere to obtain a copper-based catalyst powder with carbon layer protection; the non-oxidizing atmosphere is at least one of an inert gas, nitrogen, and carbon dioxide. The copper-based monolithic catalyst of the invention has excellent catalytic performance and stable catalytic performance, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a copper-based monolithic catalyst with carbon layer protection and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs) use hydrogen as fuel and have the advantages of high power density, low operating temperature, and almost zero pollution. They are a promising mobile power source. However, hydrogen itself has the characteristics of being difficult to compress, having a wide explosion limit, and having a low volume energy density, so its storage and transportation remain a technical challenge. Compared with direct hydrogen storage, in-situ online hydrogen production using methanol steam reforming has higher energy density and stronger safety, so it is more suitable for portable and mobile field applications.

[0003] Currently, commercial methanol hydrogen production catalysts are usually in powder or granular form, which are easy to pulverize during vehicle use, resulting in excessive pressure drop and limited mass transfer. There are also problems such as cumbersome catalyst loading process and uneven heat transfer in the reactor that affects production capacity. Using a strong thermal conductive substrate (such as silicon carbide) to load active components to construct an integral catalyst is conducive to the process intensification of the catalytic reaction and improves the activity of the catalyst.

[0004] A Chinese patent document with publication number CN110639570A discloses a method for preparing a monolithic catalyst, comprising the following steps: preparing a gel by a sol-gel method using at least one of an Al salt, a Ce salt and a Zr salt as a raw material, then immersing a porous material substrate in the gel so that the gel is uniformly loaded on the porous material substrate, sintering to obtain a catalyst precursor A in which a catalytic coating is loaded on the porous material substrate; subsequently, a solution impregnation method is used to uniformly load an oxide of active metal Cu on the catalytic coating in the catalyst precursor A, sintering to obtain a catalyst precursor B, and reducing to obtain a monolithic catalyst.

[0005] A Chinese patent document with publication number CN113000057A discloses a method for preparing a porous material loaded with a Cu / ZnO / CeO2 catalyst, comprising the following steps: S1 dissolving a copper salt, a zinc salt and a high cerium salt, adding an amide compound to obtain an impregnation solution; S2 immersing the porous material in the impregnation solution and performing microwave heating; S3 calcining the porous material; and S4 performing a reduction reaction on the porous material under a reducing atmosphere to obtain the obtained material.

[0006] The above two preparation methods have the problem of low single loading amount of catalyst active components, so repeated impregnation, drying and calcination are required. The process is complicated and cumbersome, and there are problems of poor coating firmness and uniformity, which limits the service life in the process of on-board methanol reforming hydrogen production.

[0007] The method of constructing a monolithic catalyst by integrally molding a structural base powder, active components, a binder and a pore-forming agent can simplify the production process. However, the catalytically active components are easily coated by the binder, which is not conducive to their contact with the reactants and reduces their intrinsic catalytic activity. Therefore, the catalytic activity of the catalyst prepared by this method still has room for significant improvement. Summary of the invention

[0008] The invention provides a copper-based monolithic catalyst with carbon layer protection and a preparation method thereof. The copper-based monolithic catalyst has excellent and stable catalytic performance and a long service life.

[0009] The technical solution of the present invention is as follows:

[0010] A method for preparing a copper-based monolithic catalyst with carbon layer protection, comprising: using copper-based catalyst powder with carbon layer protection, a binder, a pore-forming agent and silicon carbide as raw materials, ball-milling and mixing the raw materials uniformly, and then dry-pressing and high-temperature sintering to obtain a copper-based monolithic catalyst;

[0011] The method for preparing copper-based catalyst powder with carbon layer protection comprises:

[0012] The precursor solutions of copper salt and carrier metal salt are mixed, and an alcohol compound is added, and the catalyst precursor is obtained after drying; the catalyst precursor is heat-treated in a non-oxidizing atmosphere to obtain a copper-based catalyst powder with carbon layer protection;

[0013] The non-oxidizing atmosphere is at least one of an inert gas, nitrogen and carbon dioxide.

[0014] The present invention uses alcohol compounds to chelate copper salts and carrier metal salts, and then generates copper-based catalyst powder coated with a carbon layer by a heat treatment in-situ pyrolysis method after drying, and then uses the powder catalyst, a binder, a pore-forming agent and silicon carbide as raw materials, and mixes the materials by a mechanical ball milling method, and obtains a monolithic copper-based catalyst by dry pressing, integral molding and sintering. Thanks to the protective effect of the carbon layer on the active species, the agglomeration of the active components is reduced, and the active species are prevented from being poisoned during the molding and sintering process, which is beneficial to improving the contact between the material and the active species during the methanol steam reforming reaction, improving the mass transfer process, and thus improving the catalytic performance of the catalyst.

[0015] Preferably, the molar ratio of the copper salt, the precursor of the carrier metal salt, and the alcohol compound is (1-5):(5-9):(10-160).

[0016] Further preferably, the molar amount of the alcohol compound is 8-10 times the total molar amount of the precursor of the copper salt and the carrier metal salt. At this time, the conversion rate of methanol in the copper-based monolithic catalyst obtained is better, because the carbon layer content in the copper-based monolithic catalyst obtained under this ratio is moderate. Excessive carbon layer causes the active components to be covered, and too little carbon layer causes the active components to be unable to be completely protected. The copper-based catalyst powder obtained by the preferred technical solution has a moderate carbon layer content, showing excellent protection performance.

[0017] Preferably, the carrier is alumina and / or cerium oxide. Cu / CeO2 and Cu / Al2O3 are less affected by high temperature heat treatment and are not easily sintered during high temperature heat treatment, so they show better catalytic activity.

[0018] Preferably, the alcohol compound is at least one of ethylene glycol, propylene glycol and glycerol. Ethylene glycol, propylene glycol and glycerol have better chelation with metal salts, so that the prepared catalyst has better catalytic effect on hydrogen production by methanol steam reforming.

[0019] Preferably, the heat treatment temperature is 550-950°C and the heat treatment time is 2-5h.

[0020] The heat treatment temperature affects the product performance. Under the heat treatment conditions of 550-950℃, the amount of graphitized carbon generated is the best. Too low a heat treatment temperature results in a small amount of graphitized carbon, which decomposes into CO2 during the subsequent sintering process with silicon carbide, and has less protective effect on the active species of the catalyst. Although too high a heat treatment temperature can generate enough graphitized carbon, it also causes severe sintering of copper active species. The heat treatment time will also affect the product performance. Too long a heat treatment time causes the copper active species to sinter, the copper particle size to grow, and the catalytic activity of the final catalyst to decrease.

[0021] The heat treatment atmosphere will also affect the product performance. This is because the carbon layer is easily decomposed during heat treatment in an air atmosphere, and the active species cannot be protected during the molding process. A carbon dioxide atmosphere may cause more carbon deposits in the catalyst. Inert gases and nitrogen are neither flame retardant nor promote combustion, and both show excellent performance.

[0022] Preferably, the mass ratio of copper-based catalyst powder, binder, pore former and silicon carbide is (1-2):(0.5-1):(1-5):(4-7.5).

[0023] The raw material ratio affects the catalyst's compressive strength, methanol conversion rate, porosity and other parameters. A higher content of silicon carbide and a lower content of pore-forming agent are beneficial to improving the compressive strength, but reducing the porosity, indicating that the catalyst activity is limited by the diffusion of reactants. At the same time, this process can easily achieve a high loading of active components in the monolithic catalyst, and the catalytic activity can be significantly improved.

[0024] The adhesive is glass and / or aluminum dihydrogen phosphate. The pore-forming agent is at least one of polymethyl methacrylate (PMMA), graphite, and carbon nanotubes.

[0025] Preferably, the ball milling speed is 350-550 rpm, and the ball milling time is 0.5-8 hours. Ball milling allows the raw materials to be fully mixed and evenly mixed, and ultimately the active components in the obtained copper-based monolithic catalyst are evenly distributed, thereby improving the catalytic activity of the catalyst.

[0026] Preferably, the dry pressing pressure is 5 to 30 MPa.

[0027] Preferably, the high temperature sintering temperature is 450-1000°C; more preferably 450-800°C; more preferably 500-600°C.

[0028] The sintering temperature affects the mechanical properties and catalytic activity of the monolithic copper-based catalyst. When the sintering temperature is too low, the active component silicon carbide powder cannot be effectively bonded together, resulting in poor mechanical strength of the catalyst and easy collapse of the skeleton; when the sintering temperature is too high, the mechanical strength is enhanced, but the catalytic activity decreases. It is necessary to balance the relationship between catalyst performance and mechanical strength.

[0029] Preferably, the high temperature sintering time is 1-5 h; more preferably, it is 2-5 h.

[0030] The sintering time also affects the mechanical properties and catalytic activity of the catalyst. When the sintering time is too short, the pore-forming agent cannot be effectively removed, and the carbon layer will cover the active components, causing the catalytic activity to decrease. As the sintering time increases, the mechanical strength of the catalyst is further improved, but the catalytic activity decreases.

[0031] The present invention also provides a copper-based monolithic catalyst with carbon layer protection which is prepared by the above preparation method.

[0032] The copper-based monolithic catalyst prepared by the present invention is based on porous silicon carbide as the main body, and copper-based catalyst powder embedded in silicon carbide and protected by a carbon layer as the active component. Embedded in it means that the copper-based catalyst powder becomes a part of the main skeleton of the porous silicon carbide after high-temperature sintering. Carbon layer protection means that the C element exists in the form of one or both of graphite carbon or amorphous carbon and is coated on the active species Cu.

[0033] In the copper-based monolithic catalyst, the components are calculated by mass percentage: copper-based catalyst powder is 10-20%, binder is 5-10%, pore-forming agent is 10-50%, and silicon carbide is 40-75%.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The present invention uses organic alcohol to chelate metal ions, and heat-treats the precursor in a non-oxidizing atmosphere to promote in-situ pyrolysis of organic matter to obtain a copper-based catalyst powder coated with a carbon layer, which is then used to construct a monolithic catalyst by a subsequent one-piece molding method;

[0036] (2) Using copper-based catalyst powder coated with a carbon layer as the active component, and forming it with silicon carbide powder to construct a monolithic catalyst, the carbon layer effectively reduces the poisoning effect of glass powder on active species during the forming process, increases the copper specific surface area of ​​the catalyst, and significantly improves the catalytic activity;

[0037] (3) The copper-based monolithic catalyst of the present invention has the characteristics of high activity and low preparation cost. When used in the methanol steam reforming hydrogen production reaction, the methanol conversion rate is high and the catalytic stability is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Schematic diagram of the structure of a copper-based monolithic catalyst protected by a carbon layer;

[0039] Figure 2 This is the MSR life test data chart of the copper-based monolithic catalyst prepared in Example 2. DETAILED DESCRIPTION

[0040] Example 1

[0041] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.15 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0042] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0043] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 79% and the hydrogen selectivity was 74.5%.

[0044] Example 2

[0045] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0046] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0047] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 95% and the hydrogen selectivity was 74.9%.

[0048] Example 3

[0049] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.6 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0050] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0051] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then a methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 82% and the hydrogen selectivity was 74.3%.

[0052] Example 4

[0053] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of propylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0054] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0055] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 74% and the hydrogen selectivity was 74.2%.

[0056] Example 5

[0057] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of propylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0058] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0059] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 75% and the hydrogen selectivity was 74.2%.

[0060] Example 6

[0061] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Ce(NO3)3·6H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110 °C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750 °C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0062] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0063] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 81% and the hydrogen selectivity was 74.1%.

[0064] Example 7

[0065] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110 °C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 450 °C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0066] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0067] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 68% and the hydrogen selectivity was 74.5%.

[0068] Example 8

[0069] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 950°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0070] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0071] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 83% and the hydrogen selectivity was 74.2%.

[0072] Example 9

[0073] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 5 h to obtain a powder catalyst rich in a carbon layer.

[0074] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0075] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 84% ​​and the hydrogen selectivity was 74.7%.

[0076] Example 10

[0077] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under a CO2 atmosphere for 3 h to obtain a powder catalyst with an excess carbon layer.

[0078] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0079] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 78% and the hydrogen selectivity was 74.6%.

[0080] Embodiment 11

[0081] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under a nitrogen atmosphere for 3 h to obtain a powder catalyst with an excess carbon layer.

[0082] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0083] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 89% and the hydrogen selectivity was 74.3%.

[0084] Comparative Example 1

[0085] Commercial CuZnAl catalyst powder, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is put into a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for methanol steam reforming to produce hydrogen is obtained.

[0086] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 14% and the hydrogen selectivity was 74.3%.

[0087] Comparative Example 2

[0088] The CuO / Al2O3 powder catalyst, glass material, PMMA and silicon carbide powder prepared by co-precipitation method were accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder. The mixed powder was placed in a mold for dry pressing and sintered at 500°C to obtain an integral copper-based catalyst for hydrogen production by methanol steam reforming.

[0089] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 45% and the hydrogen selectivity was 74.2%.

[0090] Comparative Example 3

[0091] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Zn(NO3)3·6H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110 °C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750 °C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0092] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0093] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 39% and the hydrogen selectivity was 73.3%.

[0094] Comparative Example 4

[0095] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under air atmosphere for 3 h to obtain a powder catalyst without a carbon layer.

[0096] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0097] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 66% and the hydrogen selectivity was 72.8%.

[0098] Comparative Example 5

[0099] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of ethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0100] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing and sintered at 750°C to obtain an integral copper-based catalyst for hydrogen production by methanol steam reforming.

[0101] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 49% and the hydrogen selectivity was 74.1%.

[0102] Comparative Example 6

[0103] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of sorbitol, stir for 20 min, mix evenly, place in an oven at 110 °C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750 °C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0104] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0105] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 59% and the hydrogen selectivity was 72.2%.

[0106] Comparative Example 7

[0107] Weigh 0.015 mol of Cu(NO3)2·3H2O and 0.035 mol of Al(NO3)3·9H2O and dissolve them in 50 mL of deionized water, then add 0.45 mol of diethylene glycol, stir for 20 min, mix evenly, place in an oven at 110°C to dry into a dry powder state to obtain a precursor powder, and then heat treat at 750°C in a tubular furnace under argon atmosphere for 3 h to obtain a powder catalyst rich in a carbon layer.

[0108] Powdered catalyst, glass material, PMMA and silicon carbide powder are accurately weighed in a mass ratio of 1:0.5:5:4, and mixed evenly by mechanical ball milling to obtain a catalyst mixed powder, which is then placed in a mold for dry pressing. After high-temperature sintering at 500°C, an integral copper-based catalyst for hydrogen production by methanol steam reforming is obtained.

[0109] The above-mentioned integral catalyst was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography, and the methanol conversion rate was 63% and the hydrogen selectivity was 72.7%.

[0110] The comparison of the preparation conditions and performance parameters of the copper-based monolithic catalysts in Examples 1-11 and Comparative Examples 1-7 is shown in Table 1.

[0111] Table 1

[0112]

[0113] By comparing Examples 1, 2 and 3, it is found that when the amount of alcohol organic matter added is 9 times the total molar amount of metal salt, the methanol conversion rate of the monolithic catalyst is optimal, which is due to the optimal carbon content in the monolithic catalyst obtained at this ratio. Excessive carbon layer causes the active components to be covered, and too little carbon causes the active components to be unable to be completely protected. The powder catalyst obtained with 9 times the molar amount of metal salt has a moderate carbon layer content, showing excellent protection performance, and has unique advantages in the process of preparing monolithic copper-based catalysts by one-pot method.

[0114] By comparing Examples 2, 4, 5 and Comparative Examples 6 and 7, it was found that the type of alcohol organic matter affects the performance of the final integral catalyst. In the experiment of using it for methanol steam reforming to produce hydrogen, the final conversion rate was as high as 95%. Compared with other alcohols, the use of ethylene glycol to prepare the catalyst has a better effect, which may be related to the chelating effect between ethylene glycol and metal salts. The product is affected by the amount of hydroxyl groups and the number of carbon atoms.

[0115] By comparing Examples 2, 6, and Comparative Example 3, it is found that the properties of the carrier affect the activity of the integral catalyst. Cu and Zn are easily sintered at high temperatures, resulting in a serious decrease in activity; while CuCe and CuAl are less affected by high-temperature sintering and therefore exhibit better activity.

[0116] By comparing Examples 2, 7 and 8, it was found that the heat treatment temperature affects the product properties. It may be that under the heat treatment condition of 750°C, the amount of graphitized carbon generated is optimal. Too low a temperature (450°C) results in a small amount of graphitized carbon, which decomposes into CO2 during the subsequent silicon carbide sintering process and has less protective effect on the catalyst. Although too high a heat treatment temperature allows the generation of a sufficient graphitized carbon layer, it also causes severe sintering of the copper species.

[0117] By comparing Examples 2 and 9, it was found that the heat treatment time affects the product performance. If the heat treatment time is too long, the copper species will be sintered, the copper particle size will increase, and the catalytic activity will decrease.

[0118] By comparing Examples 2, 10, 11 and Comparative Example 4, it was found that the heat treatment atmosphere affects the product performance. This is because the carbon layer is easily decomposed during heat treatment under an air atmosphere, and the carbon species cannot be protected during the molding process; a carbon dioxide atmosphere may cause more carbon deposits in the catalyst; argon and nitrogen are neither flame retardant nor promote combustion, and both show excellent performance.

[0119] By comparing Example 2 with Comparative Examples 1 and 2, it can be seen that the powder catalyst rich in graphitized carbon layer is prepared into a monolithic catalyst through one-piece molding, and its catalyst performance is significantly better than the commercial CuZnAl catalyst and the Cu / Al2O3 catalyst (carbon-free) prepared by co-precipitation method, which undoubtedly reflects the importance of carbon layer in protecting active species.

[0120] By comparing Example 2 and Comparative Example 5, it can be found that the sintering temperature has a great influence on the compressive strength and methanol conversion rate of the monolithic catalyst. When the sintering temperature is 500°C, the methanol conversion rate is 95%; when the sintering temperature is 750°C, the methanol conversion rate drops to 49%, indicating that the catalyst activity is affected by high temperature. It is worth noting that with the increase of sintering temperature, the compressive strength of the catalyst is significantly improved, so it is necessary to balance the relationship between catalyst performance and mechanical strength.

[0121] The Cu specific surface areas of the copper-based monolithic catalysts prepared in Example 2 and Comparative Example 3 are shown in Table 2. The Cu specific surface areas were measured by N2O titration.

[0122] Table 2

[0123]

[0124] The schematic diagram of the structure of the copper-based monolithic catalyst with carbon layer protection prepared by the present invention is as follows Figure 1 As shown, a Cu / Al2O3 powder catalyst coated with a carbon layer is used as an active component and is integrally formed with silicon carbide powder to construct an integral catalyst. During the forming process, the carbon layer effectively reduces the poisoning effect of glass powder on active species, increases the copper specific surface area of ​​the catalyst, and significantly improves the catalytic activity.

[0125] The monolithic catalyst prepared in Example 2 was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250° C. for 3 h, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography. The results are as follows: Figure 2 As shown, it is shown that the copper-based monolithic catalyst prepared by the preparation method of the present invention has stable catalytic performance and a long service life.

[0126] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a copper-based monolithic catalyst having a carbon layer protection, characterized in that: include: The copper-based catalyst powder with carbon layer protection, binder, pore former and silicon carbide are used as raw materials, the raw materials are ball-milled and mixed evenly, and then dry-pressed and sintered at a high temperature of 450-600°C to obtain a copper-based monolithic catalyst; The method for preparing copper-based catalyst powder with carbon layer protection comprises: The precursor solutions of copper salt and carrier metal salt are mixed, and an alcohol compound is added, and the catalyst precursor is obtained after drying; the catalyst precursor is heat-treated in a non-oxidizing atmosphere to obtain a copper-based catalyst powder with carbon layer protection; The carrier formed by the precursor of the carrier metal salt is aluminum oxide and / or cerium oxide; the alcohol compound is at least one of ethylene glycol, propylene glycol and glycerol; The non-oxidizing atmosphere is at least one of an inert gas, nitrogen and carbon dioxide.

2. The method for preparing a copper-based monolithic catalyst having carbon layer protection according to claim 1, characterized in that: The molar ratio of the copper salt, the precursor of the carrier metal salt and the alcohol compound is (1-5): (5-9): (10-160).

3. The method for preparing a copper-based monolithic catalyst having carbon layer protection according to claim 1, characterized in that: The heat treatment temperature is 550-950°C; the heat treatment time is 2-5 h.

4. The method for preparing a copper-based monolithic catalyst having carbon layer protection according to claim 1, characterized in that: The mass ratio of copper-based catalyst powder, binder, pore former and silicon carbide is (1-2):(0.5-1):(1-5):(4-7.5).

5. The method for preparing a copper-based monolithic catalyst having carbon layer protection according to claim 1, characterized in that: The binder is glass and / or aluminum dihydrogen phosphate; the pore-forming agent is at least one of polymethyl methacrylate, graphite and carbon nanotubes.

6. The method for preparing a copper-based monolithic catalyst having carbon layer protection according to claim 1, characterized in that: The ball milling speed was 350~550 rpm, and the ball milling time was 0.5~8 h.

7. The method for preparing a copper-based monolithic catalyst with carbon layer protection according to claim 1, characterized in that: The high temperature sintering time is 1-5h.

8. A copper-based monolithic catalyst having a carbon layer protection, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Monolithic catalyst and preparation method and application thereof, and method for producing hydrogen by methanol steam reforming by using monolithic catalyst

    CN110639570A

  • Preparation method and application of porous material loaded with Cu / ZnO / CeO2 catalyst

    CN113000057A

  • Preparation method and application of solvent coordination metal catalyst

    CN112844446A

  • Copper-based catalyst for catalytic hydrogenation of ethylene carbonate, preparation method and application thereof

    CN113769741A